Introduction to AUD Letters and Strengthening the Community's Sense of Nationalism - Erwin Hamonangan Pane; Nur Hakima Akhirani Nasution (PT Inovasi Pratama Internasional, 2023)
The low nationalism in young generations can just happen because of various factors. They No longer live and experience the consequences of colonialism and poverty. They will not again experience treatment discrimination from other nations. Apart from that, the Globalization Trend is making the world a big village, and we can just grow indifference to nationalism as an Indonesian nation. The amount of corruption and examples that are not Good from leaders naturally also affects attitudes toward nationalism among young people. Method which is used in implementation activity This is method Watch Together (Nobar) together with public target (children, teenagers, and children ages early) For growing concern and flavor nationalism in society. Target strategic in activity: this is child teenager as well as child-cchild age early, which is in the village of Cape Siran Subdistrict Ulu Barumun Regency Padang Old as target direct. Activity devotion to the public with the theme